2020
DOI: 10.21037/jtd-20-2165
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of less invasive approach to ascending aorta and aortic root surgery

Abstract: Background: Minimally invasive aortic valve (AV) surgery has become widely accepted alternative to standard sternotomy. Despite possible reduction in morbidity, this approach is not routinely performed for aortic surgery. Current report aimed to demonstrate early and mid-term outcomes in patients undergoing minimally invasive aortic root-and ascending aorta-replacement with or without concomitant AV replacement (AVR). Methods: Between 2011 and 2018, 167 selected low-and intermediate risk patients (mean age: 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…On the other hand, doing an L-shaped MS increases the exposure of the proximal and distal aortic arch as well as the aortic root. A V or inverted T-shaped upper MS has been also reported by some groups [2,3]. While this access certainly improves visualization, it may reduce postoperative sternal stability and be associated with an increased risk of both left and right mammary arteries injury.…”
Section: Upper Msmentioning
confidence: 70%
See 1 more Smart Citation
“…On the other hand, doing an L-shaped MS increases the exposure of the proximal and distal aortic arch as well as the aortic root. A V or inverted T-shaped upper MS has been also reported by some groups [2,3]. While this access certainly improves visualization, it may reduce postoperative sternal stability and be associated with an increased risk of both left and right mammary arteries injury.…”
Section: Upper Msmentioning
confidence: 70%
“…Current evidence on MIAS is limited to retrospective observational studies since no well-powered randomized controlled trial comparing less invasive approaches and conventional surgery has been performed (Table 1). The largest single-center series on mini ascending and root interventions showed that MIAS is a safe and efficacious procedure and is associated with excellent outcomes, in selected patients [3,17,20,22,25]. Early mortality ranges from 0 to 1%, with a stroke rate of 0.6-1%.…”
Section: Ascending Aorta and Root Surgerymentioning
confidence: 99%
“…Inoue et al reported T-shaped hemisternotomy instead of L-shaped hemisternotomy as a standard incision procedure ( 11 ). Staromłyński et al reported hemi-arch replacement through V-shaped hemisternotomy with an incision of only 6 cm ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short-and long-term mortality was 1% and 5%, respectively. Seven % reoperations for bleeding, 1.7% prolonged ICU stays and 4.8% postoperative AKIs were observed [23].…”
Section: Aortic Valve Repair and Valve-sparing Procedures Through A M...mentioning
confidence: 96%